An improved measurement of B°-B° mixing in Z° decays - Dova, María Teresa (1992)
A more precise determination of the B°-B ° mixing parameter in Z ° decays based on a fourfold increase in statistics has been made using the 1990 and t99t L3 data. The analysis of the dilepton events, rnuons and electrons, gives: Za = 0.121 + 0.017 (stat) :t: 0.006 (sys). Using the value Of Xd measured at the "f(4S) we derive the following limit for Zs: Zs > 0.16 (90% CL).